2016
DOI: 10.1162/jocn_a_00995
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Parallel Attentional Selection Can Be Controlled by Shape and Alphanumerical Category

Abstract: This is a manuscript version of the article which has been accepted for publication in Journal of Cognitive Neuroscience. Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…These observations suggest that colour-guided attentional selection processes can operate in parallel for multiple target objects at different locations, with each selection process following its own independent time course. Such rapid and apparently parallel attentional target selection processes are not confined to tasks where attention is guided by colour, as very similar temporal patterns of N2pc components were also found in a task with shape-defined targets, and even when targets were defined by their alphanumerical category (Jenkins, Grubert, & Eimer, 2016). …”
mentioning
confidence: 65%
See 2 more Smart Citations
“…These observations suggest that colour-guided attentional selection processes can operate in parallel for multiple target objects at different locations, with each selection process following its own independent time course. Such rapid and apparently parallel attentional target selection processes are not confined to tasks where attention is guided by colour, as very similar temporal patterns of N2pc components were also found in a task with shape-defined targets, and even when targets were defined by their alphanumerical category (Jenkins, Grubert, & Eimer, 2016). …”
mentioning
confidence: 65%
“…All participants had normal or corrected-to-normal vision. This choice of sample size (n=12 after excluding three participants) was based on a power analysis that 8 employed the effect size obtained from a previous N2pc experiment in our lab (Jenkins, Grubert, & Eimer, 2016), in which the same sample size was used to compare N2pc onset latencies across multiple displays and SOA conditions in response to rapidly presented shape-defined target stimuli. 1…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be overcome by presenting one of these targets on the vertical meridian (above or below fixation). Because vertical targets do not elicit N2pc components, the N2pc will exclusively reflect the selection of the horizontal target, independently of any additional attentional processing of the vertical target object (e.g., Eimer & Grubert, 2014;Eimer, Kiss, & Nicholas, 2011;Hickey, Di Lollo, & McDonald, 2009;Hickey, McDonald, & Theeuwes, 2006;Woodman, & Luck, 1999;Eimer & Grubert, 2014;Grubert & Eimer, 2015, 2016aJenkins, Grubert, & Eimer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…If allocating attention to a template-matching object in the first display always resulted in an inhibition of a second attentional selection process, the N2pc to target objects in the second display should have been strongly attenuated in these blocks, which was clearly not the case. Finally, and most importantly, in earlier N2pc studies that used analogous D1-D2 presentation sequences (Eimer & Grubert, 2014;Jenkins et al, in press), both displays contained task-relevant objects that had to be identified. When these two displays were separated by an SOA of 100 ms, as in the present study, target objects in the second display elicited solid N2pc components that were equal in size to the N2pc triggered by targets in the first display (as illustrated in Figure 1D).…”
mentioning
confidence: 98%